BIMBINGAN DAN KONSELING BERPERILAKU NAKAL PESERTA DIDIK - Sari, Eka Novita (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study aims to reveal the perceptions of elementary school teachers regarding student delinquency. This study used a qualitative approach, with a phenomenological case study design. The data analysis used was phenomenological analysis. The results of research on perceptions of elementary school teachers of "NEGERI AGOM" about student delinquency, namely: (1) student delinquency is a deviant and violates school rules committed by students, thus disturbing the learning environment and harming other individuals. (2) the form of student delinquency was categorized into 2, namely disruptive behavior and serious delinquency. Disturbing behavior is perceived in various ways including: not paying attention to tidiness, not paying attention to teacher explanations, cheating, making physical threats to students and disobeying teacher directions, nagging (still talking and not admitting mistakes), while serious student delinquency includes: truancy and chasing behavior. . (3) the causes of student's condition, namely: physical condition, lack of parental attention, less varied teacher learning methods, language difficult to understand by students, negative environment and too much lesson material. (4) how to deal with student delinquency, namely: providing learning models for students, verbal warning, special attention, providing special understanding, providing seating manipulation, providing learning grids, communicating with parents, providing rules, providing motivation, communicating online private with students, and returned to parents.